Synthesis of Dichloro-Palladium-4-(2,5-Dibromo Imidazolyl)- 2′-Amino Pyridyl Complex As Pre-Catalyst And Its Application In Suzuki-Miyaura Cross Coupling Reaction - Hashem, Md Abul; Akter, Mosammat Hasina; Farhana, Fatiha (Journal of the Bangladesh Chemical Society, 2012)
4-(2,5-Dibromoimidazolyl)-2?-aminopyridyl form complex with Na2PdCl4 in methanol. 1 mmol% of the complex was utilized in Suzuki-Miyaura cross coupling reaction to prepare substituted biphenyls and terphenyls in good to excellent yields. DOI: http://dx.doi.org/10.3329/jbcs.v25i1.11779 Journal of Bangladesh Chemical Society, Vol. 25(1), 87-96, 2012